2002
DOI: 10.1016/s0167-2991(02)80091-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic properties of beta zeolite exchanged with Pd and Fe for toluene total oxidation

Abstract: Dealuminated beta zeolites exchanged with Pd and Fe were prepared to investigate the influence of iron and dealumination on the activity and selectivity of Pd/BEA zeolite for toluene total oxidation. The specific areas determined by BET method and EPR studies allowed to know that the palladium would be more easily agglomerated on the BEA than on the DBEA. Moreover, a quantification of the palladium saturation on the BEA zeolite was deduced by EPR. Effects of dynamic and static oxidation and weak and strong red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The relative amounts of Pd + and Pd 2+ cations exchanged at NNN Al pairs can therefore be altered by varying the temperature and partial pressure of water. The question of whether or not Pd + is present in as-prepared and pretreated Pd/CHA remains open, as several authors have suggested based on evidence inferred from IR spectroscopy that Pd + only forms upon NO adsorption via the process Pd 2+ (Z -) 2 + 2 NO → (NO) Pd + Z -+ NO + Z -; however, direct evidence of Pd + in zeolites in the absence of adsorbates has been reported by electron paramagnetic resonance spectroscopy (EPR) [15,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…The relative amounts of Pd + and Pd 2+ cations exchanged at NNN Al pairs can therefore be altered by varying the temperature and partial pressure of water. The question of whether or not Pd + is present in as-prepared and pretreated Pd/CHA remains open, as several authors have suggested based on evidence inferred from IR spectroscopy that Pd + only forms upon NO adsorption via the process Pd 2+ (Z -) 2 + 2 NO → (NO) Pd + Z -+ NO + Z -; however, direct evidence of Pd + in zeolites in the absence of adsorbates has been reported by electron paramagnetic resonance spectroscopy (EPR) [15,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…Pd + had only been observed in a small number of binuclear Pd complexes, 20 until a family of mononuclear Pd + species was very recently characterized by Luo et al 21 In the zeolite literature, Jacquemin et al have reported the presence of Pd + cations based on observation of EPR signals consistent with the presence of paramagnetic species in their study of the catalytic properties of Pd and Fe-exchanged beta zeolites for toluene oxidation. 22 In a recent study, Paolucci et al assessed the speciation of Pd in zeolites under PNA conditions using both experiments and periodic DFT calculations. 23 For Pd/H-CHA, these authors conclude that at typical loadings, Pd will occur as Pd 2+ at specific proximate Al pairs (next-next-nearest neighbors, separated by two Si atoms) in the 6-ring on the basis of the favorable energetics of Pd 2+ at this ion-exchange site, combined with a model for the Al distribution in CHA introduced in previous work.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in % TN Conv. during the preliminary oxidation time may be connected to the formation of coke [91], blocking of NiO active sites by water vapor, catalyst poisoning or fouling [92,93]. Previous studies have shown that the deactivation of the catalyst by water vapor is reversible [94][95][96].…”
Section: Stability Testsmentioning
confidence: 99%